Development of Green Economy Index (GEI) with Remote Sensing to Support Sustainable Economy in East Java - Wahidya Nurkarim (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
The green economy concept is now widely used by many countries as a development concept that supports economic growth by ensuring that natural aspects are maintained. The green economy index (GEI) was formed to provide an evaluation of the achievements of the transformation of a greener economic development. The availability of Remote Sensing data has the potential to complement data that is not available at the regional level. This study builds the GEI Index in the province of East Java using indicators that have been studied literacy. The results obtained are that the green economy index in East Java has increased over the last five years. The city of Surabaya is the center of economic development which can be seen from many indicators. This indicates that spatial effects affect sustainable development that is environmentally friendly in East Java. Regional grouping analysis gives the result that there are groups that really need special attention because of the low scores on almost all indicators. Not only the regency government but also the policy from the East Java provincial government is needed to participate in developing this green economy practice.